2021
DOI: 10.3389/fnins.2021.718230
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortical Changes Precede Brainstem Changes During Rapid Implicit Learning: Evidence From Human EEG

Abstract: The auditory system is sensitive to stimulus regularities such as frequently occurring sounds and sound combinations. Evidence of regularity detection can be seen in how neurons across the auditory network, from brainstem to cortex, respond to the statistical properties of the soundscape, and in the rapid learning of recurring patterns in their environment by children and adults. Although rapid auditory learning is presumed to involve functional changes to the auditory network, the chronology and directionalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Neuroimaging research has, on the whole, been more invested into contrastive comparisons (e.g., Bonte et al, 2017;Erb et al, 2013b;Guediche et al, 2015;Myers & Mesite, 2014): questions about the involvement of different types of information processing-operationalized as differential activation of different brain areas and networks that are associated with different functionality-are the bread and butter of neuroimaging. This approach has identified a wide range of brain regions as involved in different aspects of adaptive speech perception, ranging from subcortical areas (e.g., Guediche et al, 2015;Skoe et al, 2021) to networks associated with decision-making (e.g., Erb et al, 2013b;Myers & Mesite, 2014). This leaves open, however, what types of computations underlie the observed differential activations, or why different types of exposure lead to different types of behavioral changes.…”
Section: The State Of the Field(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging research has, on the whole, been more invested into contrastive comparisons (e.g., Bonte et al, 2017;Erb et al, 2013b;Guediche et al, 2015;Myers & Mesite, 2014): questions about the involvement of different types of information processing-operationalized as differential activation of different brain areas and networks that are associated with different functionality-are the bread and butter of neuroimaging. This approach has identified a wide range of brain regions as involved in different aspects of adaptive speech perception, ranging from subcortical areas (e.g., Guediche et al, 2015;Skoe et al, 2021) to networks associated with decision-making (e.g., Erb et al, 2013b;Myers & Mesite, 2014). This leaves open, however, what types of computations underlie the observed differential activations, or why different types of exposure lead to different types of behavioral changes.…”
Section: The State Of the Field(s)mentioning
confidence: 99%
“…In contrast to the assumption that cross-talker variability may be learned and stored, which is fundamental to all the theories of representational changes as described above, normalization proposals assume that listeners remove talker variability prior to mapping cues to linguistic categories. More recently, evidence from neuroimaging studies has lent support for low-level normalization mechanisms by showing engagement of subcortical structures in sensory adaptation (e.g., the brain stem, Skoe et al, 2021;and cerebellum, Guediche et al, 2015; for review, see Guediche et al, 2014). Studies using intracranial electrocorticography have found evidence of talker-normalized (spectral) cues in the auditory cortex before they are mapped onto categories (e.g., Sjerps et al, 2019;Tang et al, 2017a).…”
Section: The State Of the Field(s)mentioning
confidence: 99%
“…This notion aligns with recent studies suggesting cortical changes precede those in brainstem (Reetzke et al . 2018; Skoe et al 2021) by several days/weeks, as well as theoretical accounts that learning proceeds in a top-down guided manner (Ahissar and Hochstein 2004), with sensory change in the brainstem only emerging at expert stages of learning (Reetzke et al . 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that auditory plasticity is stronger and emerges earlier at cortical relative to brainstem levels (e.g., Reetzke et al . 2018; Skoe et al . 2021; Bidelman et al .…”
Section: Discussionmentioning
confidence: 99%
“…In ferrets, changes in non-primary auditory cortex neurons precede changes in primary auditory cortex (Elgueda et al, 2019 ). In humans, non-primary AC has a larger influence than primary AC on speech perception (Hamilton et al, 2021 ), and cortical changes precede midbrain changes as demonstrated by Skoe et al's contribution to this issue (Skoe et al, 2021 ).…”
mentioning
confidence: 99%